2019
DOI: 10.1037/ccp0000405
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and mediators of a group cognitive–behavioral therapy for hoarding disorder: A randomized trial.

Abstract: Objective: Hoarding disorder (HD) is a common and potentially debilitating psychiatric disorder. Thus far, psychological treatments have yielded modest effects and/or were time-consuming and costly to deliver. The aim of the present study was to test the efficacy of a brief group cognitive-behavioral therapy (CBT) for adults with HD and to test hypothesized mediators of treatment outcome. Method: Eighty-seven adults with a primary diagnosis of HD were randomized to either immediate CBT or wait list. CBT consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 68 publications
1
27
0
1
Order By: Relevance
“…Across the three cases, one patient declined treatment, while the other two experienced modest improvements in HD symptoms. This finding is consistent with the wider literature where dropout rates can range from 13% [21] to 30% [22], and even after best-practice CBT treatment many patients with HD remain symptomatic despite reducing their symptoms significantly [8]. Reflecting this, multiple new directions for research are being investigated to enhance the efficacy of CBT for HD including adding a contingency management approach to treatment [23] and between-session internet-based clinician support [24] and such strategies may enhance outcomes in patients who have HD and comorbid HF or other cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Across the three cases, one patient declined treatment, while the other two experienced modest improvements in HD symptoms. This finding is consistent with the wider literature where dropout rates can range from 13% [21] to 30% [22], and even after best-practice CBT treatment many patients with HD remain symptomatic despite reducing their symptoms significantly [8]. Reflecting this, multiple new directions for research are being investigated to enhance the efficacy of CBT for HD including adding a contingency management approach to treatment [23] and between-session internet-based clinician support [24] and such strategies may enhance outcomes in patients who have HD and comorbid HF or other cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 93%
“…More recently, Levy et al (2017) found that changes in maladaptive saving cognitions mediated symptom improvement in CBT for HD. This finding was partially replicated in a study of mediators of treatment response in group CBT for HD (Tolin et al, 2019).…”
Section: Attrition and Response To Treatmentmentioning
confidence: 77%
“…Integrating an intervention that targets increasing readiness for change, such as motivational interviewing (MI), with HD treatment might result in improved treatment response and should be explored in further research with HD. MI augmented behavior therapy has already been implemented with children and adults with OCD (Merlo et al, 2010;Simpson, Zuckoff, Page, Franklin & Foa, 2008) as well as in one trial with HD individuals (Tolin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…CBT for hoarding disorder: A group therapy program therapist's guide. Wiley.—This group‐based manual was effective in a recent RCT (Tolin et al, submitted for publication).…”
Section: Existing Treatment Guidelinesmentioning
confidence: 99%